2008
DOI: 10.1111/j.0018-0661.2008.02006.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL contributing to SCMV resistance in tropical maize

Abstract: Sugarcane mosaic virus (SCMV) has been increasing in importance as a maize disease in Brazil. In this study, we mapped and characterized quantitative trait loci (QTL) associated with resistance to SCMV in a maize population consisting of 150 F 2:3 families from the cross between two tropical maize inbred lines, L520 (resistant) and L19 (susceptible). F 2 individuals were genotyped with microsatellite (SSR) markers, and the derived F 2:3 families were evaluated for their response to artificial inoculation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…High-resolution mapping using progeny from the cross between FAP1360A (completely resistant to SCMV) and F7 (highly susceptible to SCMV) confirmed that Scmv1 (on the short arm of chromosome 6) and Scmv2 (near the centromere of chromosome 3) are crucial for maize resistance to SCMV [ 13 ]. Similar mapping results have been reported in several independent experiments [ 8 , 14 , 15 ]. The Scmv1 locus has also been detected in a resistant Chinese line, Huangzao4, together with additional QTL on chromosomes 1, 3, 5, and 10 [ 14 ].…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…High-resolution mapping using progeny from the cross between FAP1360A (completely resistant to SCMV) and F7 (highly susceptible to SCMV) confirmed that Scmv1 (on the short arm of chromosome 6) and Scmv2 (near the centromere of chromosome 3) are crucial for maize resistance to SCMV [ 13 ]. Similar mapping results have been reported in several independent experiments [ 8 , 14 , 15 ]. The Scmv1 locus has also been detected in a resistant Chinese line, Huangzao4, together with additional QTL on chromosomes 1, 3, 5, and 10 [ 14 ].…”
Section: Introductionsupporting
confidence: 91%
“…By using an F 9 -derived immortalized RIL population obtained from the cross of Huangzao4×Mo17, a major QTL was detected between chromosome bins 6.00 and 6.01, accounting for 50.0% of the total phenotypic variation and decreasing the disease index by 27.9% [16]. The loci on chromosomes 3 and 6 have also been confirmed in tropical maize germplasm from Brazil [15]. With the aid of the whole-genome B73 sequence, the Scmv2 region was fine-mapped to a region of 0.28 cM, covering a physical distance of 1,342.6 kb.…”
Section: Introductionmentioning
confidence: 99%
“…Gene action was mostly partially dominant or recessive. This result is accordance to Souza [25] who observed over dominance gene action for mostly region for SCMV disease in maize.…”
Section: Discussionsupporting
confidence: 93%
“…The development of molecular markers associated with economic target traits is an extremely slow process for sugarcane. Previous studies on the development of molecular markers for mosaic resistance were mainly focus on corn (2 n = 2 x = 20; genome size =~2300 Mb) [156][157][158][159][160][161][162][163][164]. However, these studies may provide a good reference for developing molecular markers and related gene mining on sugarcane.…”
Section: Acceleration Of Molecular Breedingmentioning
confidence: 99%